The longest reported sibling survivors of a severe form of congenital myasthenic syndrome with the ALG14 pathogenic variant. Issue 4 (31st December 2021) - Katata, Yu; Uneoka, Saki; Saijyo, Naoya; Aihara, Yu; Miyazoe, Takamitsu; Koyamaishi, Shun; Oikawa, Yoshitsugu; Ito, Yuya; Abe, Yu; Numata‐Uematsu, Yurika; Takayama, Jun; Kikuchi, Atsuo; et al.
Abstract: Congenital myasthenic syndromes (CMS) is a group of diseases that causes abnormalities at the neuromuscular junction owing to genetic anomalies. The pathogenic variant in ALG14 results in a severe pathological form of CMS causing end‐plate acetylcholine receptor deficiency. Here, we report the cases of two siblings with CMS associated with a novel variant in ALG14 . Immediately after birth, they showed hypotonia and multiple joint contractures with low Apgar scores. Ptosis, low‐set ears, and high‐arched palate were noted. Deep tendon reflexes were symmetrical. They showed worsening swallowing and respiratory problems; hence, nasal feeding and tracheotomy were performed. Cranial magnetic resonance imaging scans revealed delayed myelination and cerebral atrophy. Exome sequencing indicated that the siblings had novel compound heterozygous missense variants, c.590T>G (p.Val197Gly) and c.433G>A (p.Gly145Arg), in exon 4 of ALG14 . Repetitive nerve stimulation test showed an abnormal decrease in compound muscle action potential. After treatment with pyridostigmine, the time off the respirator increased. Their epileptic seizures were well controlled by anti‐epileptic drugs. Their clinical course is stable even now at the ages of 5 and 2 years, making them the longest reported survivors of a severe form of CMS with the ALG14 variant thus far.